Short-Term Exposure of Mytilus coruscus to Decreased pH and Salinity Change Impacts Immune Parameters of Their Haemocytes - Wu, Fangli; Xie, Zhe; Lan, Yawen; Dupont, Sam; Sun, Meng; Cui, Shuaikang; Huang, Xizhi; Huang, Wei; Liu, Liping; Hu, Menghong; Lu, Weiqun; Wang, Youji (Frontiers in Physiology, 2018)
With the release of large amounts of CO2, ocean acidification is intensifying and affecting aquatic organisms. In addition, salinity also plays an important role for marine organisms and ﬂuctuates greatly in estuarine and coastal ecosystem, where ocean acidification frequently occurs. In present study, flow cytometry was used to investigate immune parameters of haemocytes in the thick shell mussel Mytilus coruscus exposed to different salinities (15‰, 25‰ and 35‰) and two pH levels (7.3 and 8.1). A 7-day in vivo and a 5-hour in vitro experiments were performed. In both experiments, low pH had a significant effects on all tested immune parameters. When exposed to decreased pH, total haemocyte count (THC), phagocytosis (Pha), esterase (Est) and lysosomal content (Lyso) were significantly decreased, whereas haemocyte mortality (HM) and reactive oxygen species (ROS) were increased. High salinity had no significant effects on the immune parameters of haemocytes as compared with low salinity. However, an interaction between pH and salinity was observed in both experiments for most tested haemocyte parameters. This study showed that high salinity, low salinity and low pH have negative and interactive effects on haemocytes of mussels. As a consequence, it can be expected that the combined effect of low pH and changed salinity will have more severe effects on mussel health than predicted by single driver exposure.